Bicuspid Aortic Valve, Bovine Aortic Arch and early Atherosclerosis: When one plus one equals three - Chatzistamatiou, E; Moustakas, G; Babatseva-Vagena, I; Danelatos, C; Androulakis, A; Avgeropoulou, C; Tousoulis, D; Kallikazaros, I (Global Journal of Medical and Clinical Case Reports, 2017)
Despite that even normally functioning bicuspid aortic valves can have abnormal transvalvular-flow patterns, resulting in regional increases in wall shear stress and aortic dilatation, most often are preserved during ascending aorta replacement. On the other hand, the most common normal variant of aortic arch branching, known as bovine aortic arch, may be considered a risk factor for the development of ascending aorta dilatation, as recent studies have shown. However, data are lacking in the literature regarding the involvement of bicuspid aortic valve and/or bovine aortic arch in early atherosclerosis development. We present a case of a young female patient with bicuspid aortic valve, bovine aortic arch and advanced carotid atherosclerotic disease disproportionate to her cardiovascular risk profile and solely explained by hemodynamic alterations produced by those two ‘normal’ anatomical variations.We present a case of a young female patient with bicuspid aortic valve, bovine aortic arch and advanced carotid atherosclerotic disease disproportionate to her cardiovascular risk profile and solely explained by hemodynamic alterations produced by those two ‘normal’ anatomical variations.